Integrating AI Chatbots into Islamic Education: Effects on Students’ Self-Regulated and Learning Outcomes at SMP IT Pondok Tahfizh Qur'an Kepulauan Bangka Belitung - Sumarli Sumarli; Dian Rezki Pratama (CV. Zamron Pressindo, 2025)
Research Objective – This study aims to examine the effects of integrating AI-powered chatbots into Islamic education on students’ self-regulated learning (SRL) and learning outcomes at the junior high school level. Methodology – A quantitative quasi-experimental design with a non-equivalent control group pretest–posttest was employed. The participants were 64 eighth-grade students at SMP IT Pondok Tahfizh Qur'an Kepulauan Bangka Belitung, Indonesia, divided into an experimental group receiving AI chatbot–supported instruction and a control group receiving conventional teacher-centered instruction. Data were collected using an adapted Self-Regulated Learning questionnaire and an achievement test, and analyzed through descriptive statistics, independent-samples t-tests, gain score analysis, and Pearson correlation. Findings – The results indicate that students in the experimental group demonstrated significantly higher improvements in both self-regulated learning and learning outcomes compared to the control group (p < 0.001). A strong positive correlation was also found between SRL and learning outcomes (r = 0.68), suggesting that enhanced self-regulation contributes meaningfully to academic achievement. Research Implications/Limitations – The findings highlight the pedagogical potential of AI chatbots to foster learner autonomy and academic performance in Islamic education, although generalizability is limited by the single-institution sample. Originality/Value – This study provides novel empirical evidence on AI chatbot integration in Islamic secondary education, linking SRL development with learning outcomes within a faith-based context.